Venous ulcer: clinical assessment, guidelines and dressing care - Chara Keith Diógenes Brito; Iale Cardoso Nottingham; Janaína Fonseca Victor; Sarah Maria de Sousa Feitoza; Máguida Gomes da Silva; Heloísa Esteves Gurgel do Amaral (Rev Rene)
The objective was to analyze the clinical profile of venous ulcers, getting familiar with received recommendations and investigating healing procedures. This is an exploratory-descriptive transversal research. The sample consisted of 51 patients with venous ulcers assisted in two vascular surgery clinics in Fortaleza from August to November 2011. Results revealed the existence of venous ulcer for more than one year in 60.8% of cases being that 44.1% of them suffered at least one relapse. The most important healing initiatives according to the patients were: rest (45.1%), limb elevation (23.5%) dressing application (19.6%). As for the place in which the dressing was prepared, 76.5% mentioned home as the primary location. It is suggested that further research on guidelines and dressing care should be carried out, as it is only through researchers’ adherence to guidelines in different scenarios that we can learn more about venous ulcer care.